2019
DOI: 10.3324/haematol.2019.220988
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein Ib clustering in platelets can be inhibited by α-linolenic acid as revealed by cryo-electron tomography

Abstract: Platelet adhesion to the sub-endothelial matrix and damaged endothelium occurs through a multi-step process mediated in the initial phase by glycoprotein Ib binding to von Willebrand factor, which leads to the subsequent formation of a platelet plug. The plant-derived omega-3 fatty acid alpha-linolenic acid is an abundant alternative to fish-derived n-3 FA and has antiinflammatory and anti-thrombotic properties. In this study, we investigated the impact of alpha-linolenic acid on human platelet binding to vWF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
4
13
0
Order By: Relevance
“…Indeed, lifelong dietary ALA decreased some genera belonging to the phyla Proteobacteria including Desulfovibrio and Firmicutes including Clostridia_VadinBB60 group , which both are known to be positively associated with inflammatory responses during aging process ( Fu et al., 2020 ; Zou et al., 2020 ; Burrello et al., 2018 ; Conley et al., 2016 ). Based on the current findings that a lifelong high ALA diet could decrease plasma TMAO levels within old mice and on our previous studies showing that ALA interferes with clustering of GPIb receptors on platelet surface under high-shear rates ( Stivala et al., 2020 ), we indicate that ALA may modulate both directly, via amelioration of platelet reactivity and adhesion to vWF and decrease in procoagulant factors, and indirectly, via the reduction of TMAO production and inflammatory cytokines and increase in SCFA acetate.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Indeed, lifelong dietary ALA decreased some genera belonging to the phyla Proteobacteria including Desulfovibrio and Firmicutes including Clostridia_VadinBB60 group , which both are known to be positively associated with inflammatory responses during aging process ( Fu et al., 2020 ; Zou et al., 2020 ; Burrello et al., 2018 ; Conley et al., 2016 ). Based on the current findings that a lifelong high ALA diet could decrease plasma TMAO levels within old mice and on our previous studies showing that ALA interferes with clustering of GPIb receptors on platelet surface under high-shear rates ( Stivala et al., 2020 ), we indicate that ALA may modulate both directly, via amelioration of platelet reactivity and adhesion to vWF and decrease in procoagulant factors, and indirectly, via the reduction of TMAO production and inflammatory cytokines and increase in SCFA acetate.…”
Section: Discussionsupporting
confidence: 59%
“…Impedance platelet aggregometry assays were performed as previously described ( Stivala et al., 2020 ). In brief, whole blood was collected from old (>18-month-old) or young (2-3-month-old) mice under different treatments using sodium citrate (0.109 M).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ALA was not associated with the prevalence of LNCCIs or markers of small vessel disease. Previous studies reported that ALA improved endothelial function [ 30 ], reduced vascular inflammation [ 12 ], and inhibited platelet adhesion and aggregation [ 31 , 32 ]. The well-described anti-inflammatory and anti-thrombotic effects in vitro and in rodents, however, did not translate to significant clinical results.…”
Section: Discussionmentioning
confidence: 99%